Long-term use of glucocorticoid exacerbates bone lesions in postmenopausal women with rheumatoid arthritis. Issue 1 (25th September 2021) - Hatano, Masaki; Kitajima, Izuru; Nakamura, Masaki; Isawa, Kazuya; Suwabe, Tatsuya; Hoshino, Junichi; Kinowaki, Keiichi; Ohashi, Kenichi; Sawa, Naoki; Yamamoto, Seizo; Ubara, Yoshifumi
ABSTRACT: Glucocorticoid-induced osteoporosis is osteoporosis arising due to long-term use of glucocorticoids. Despite decades of intense research, the effects of long-term use of glucocorticoids in humans on bone cells and bone structural changes remain unclear. We performed post-mortem histomorphometric analysis of bone from two female patients with rheumatoid arthritis aged 64 and 85 years. Our two patients had been treated with glucocorticoids for 19 and 14 years, respectively. In Case 1, all markers of cancellous bone volume were markedly decreased compared with the age-matched reference range. Connectivity of cancellous bone trabecula was absent. Only a few island bones were noted. There was prominent thinning of the cortical bone and extension of the bone marrow cavity into the cortical bone with prominent cortical porosis. Cortical nodes between the endocortical surface and the trabecula disappeared due to endocortical resorption. Stoppage of lamellar structure was observed because the bone resorption by osteoclasts surpassed bone formation by osteoblasts. Empty lacunae characterised by disappearance of osteocytes were visible. In Case 2, all volume markers of cancellous bone were decreased to the same extent as Case 1. However, cortical porosis was more prominent than Case 1. These two cases suggest that use of glucocorticoid therapy >10 years can induce severe osteoporosis in elderly rheumatoid arthritis women with higher disease activity and that the disappearance of cancellous bone is the common characteristic. The 85-year-old woman was characterised by cortical porosis.